SYNTACTICAL ANALYSIS OF ANIMAL-RELATED RIDDLES IN ENGLISH AND UZBEK (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the syntactical structures of animal-related riddles in English and Uzbek. It analyzes the similarities and differences in syntactic patterns, word order, and stylistic devices used in these riddles across the two languages. The study aims to highlight how cultural factors and linguistic characteristics influence the formation and interpretation of riddles.